(3cJGH GdQhVGJ GdeRgQGJ aj GdYed HQHY GdebfWQGJs - (3eMeO Hf CMeO Hf YHO GdQMje GdeRj GdeGdcj , TeS GdOjf,J (B750 (3g` s ((3CMeO Hf GHQGgje GdSWMi s)
(3ChdgG (B:s
(3bGd GdTjN GdeRi GdeGdci hHYO aEfg deG cGf Yde GdhbJ efOhHkG Edjg hGdeYhd ai HYV TQhW UMI GdUdGI Ydjg hLH TQM GdJhUd Edjg HCSgd GdGdGJ hgh QHY GdOGFQI GdehVhY Ydjg GdebfWQGJ s
(3BNQgG (B:s
(3hbO CKHJfG LejY eG jMJGL Edjg GdeTJZd HgPg GdGdI eNJUQkG adjcf gPG BNQ GdQSGdI JeJ GdQSGdI HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG s
Keywords: (3Gdadcs